Analisis Penyelesaian Aksi Mogok Kerja Karyawan PT. Swakarya Indah Di Kota Tanjungpinang Tahun 2023 - Wulansari, Rindi; Habibi, Alif Farhan; Naufal, Muhammad; Candra, Mellyana (CV. ITTC INDONESIA, 2023)
Abstracts are written in English and Indonesian (except articles written in English) which contain the main issues, research Disputes that occur in the world of work are not difficult to encounter. Disputes that occur can also involve various kinds of problems between workers or labor unions and the company. Problems in industrial relations must find a way out so that they can be resolved. This research aims to analyze the resolution of the strike action carried out by PT employees. Beautiful DIY Clothing. The method used in this research study is literature study. The data source obtained in this research was by reading and studying what happened in the field based on facts. The results of this research were strike actions carried out by employees of PT. Swakarya Indah Busana is a salary arrears that have not been paid by the company for three months. Bipartite settlement efforts between union representatives and company leadership.